Symbolic dimensions of the night and the palm tree in the poetry of the contemporary dune region - abbas, salima; doghmane, ali (El Omda in Linguistics and Discourse Analysis, 2024)
This study aims at knowing the methods of forming the symbols in the contemporary Algerian Saharan poem. These symbols include the night and the palm tree that allow the poet to express what he wants because they are two important elements of the Saharan nature. Thus, the poets depicted and used them in their works. In this line, he who is interested in the Algerian sand dunes poetry finds that it is rich with the images of the night and the palm tree as they are two important sources for the poets’ inspiration and for the depiction of the life in the Sahara. Thus, this paper shall shed light on the methods used for the night and the palm tree and on their ability to depict the Saharan nature. Moreover, we reveal what the two symbols refer to according to the use of the poet. Based on what has been said, we raise the following problematic: “what are the semantics of the use of the night and palm tree by the contemporary Algerian Saharan poet?”